Suppressing Energetic Disorder Enables Efficient Indoor Organic Photovoltaic Cells With a PTV Derivative - Bi, Pengqing; Ren, Junzhen; Zhang, Shaoqing; Zhang, Tao; Xu, Ye; Cui, Yong; Qin, Jinzhao; Hou, Jianhui (Frontiers in Chemistry, 2021)
Indoor organic photovoltaics (IOPVs) cells have attracted considerable attention in the past few years. Herein, two PTV-derivatives, PTVT-V and PTVT-T, were used to fabricate IOPV cells with ITCC as acceptor. The molecular crystallinity orientation changed from edge-on to face-on after replacing the ethylene in the backbones of PTVT-V by the thiophene in that of PTVT-T. Besides, it was found that, the energetic disorder of the PTVT-T:ITCC based system is 58 meV, which in much lower than that of PTVT-V:ITCC-based system (70 meV). The lower energetic disorder in PTVT-T:ITCC leads to an efficient charge transfer, charge transport and thus the weak charge recombination. As a result, a PCE of 9.60% under AM 1.5G and a PCE of 24.27% under 1000 lux (LED 2700 K) with a low non-radiative energy loss of 0.210 eV were obtained based on PTVT-T:ITCC blend. The results indicate that improve the PTV-derivatives photovoltaic properties by suppressing the energetic disorder is a promising way to realize low-cost IOPV cells.